Cognitive correlates of mixed depression - A. Simonetti; E. Bernardi; G. Bartolucci; O. Ferrara; S. Ruggiero; M. Di Nicola; D. Janiri; G. Sani (European Psychiatry, 2022)
Introduction Mixed depressive states portend greater rates of impulsivity, attempted suicide, treatment resistance, and poorer outcome than non-mixed forms of depression. The neurocognitive bases of such affective states have not been defined yet.